Pemanfaatan Limbah Dapur Menjadi Eco Enzyme Dan Lilin Aromaterapi Di Desa Mekar Jaya, Kabupaten Tangerang - Qeis Bayu Pamungkas; Anggreini Salsabilla; Fakhru Rizki Ramadhan; Leis Suzanawaty (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The household waste problem, particularly organic waste and used cooking oil, had become an environmental issue contributing to pollution and decreased community health. This research was conducted in Mekar Jaya Village, Panongan District, Tangerang Regency, with the aim of empowering the community through the utilization of kitchen waste into environmentally friendly products. The approach employed was Participatory Action Research (PAR), which emphasized active community involvement at every stage, including planning, action, and reflection. Training sessions on producing eco-enzyme from orange peels were carried out with the participation of the GENTA Community, while the creation of aromatherapy candles from used cooking oil was guided directly by researchers. The results indicated high community participation, with increased enthusiasm particularly for making aromatherapy candles due to their economic potential. Meanwhile, eco-enzyme was appreciated for its benefits in household cleaning and environmental health, despite requiring fermentation time. Collective reflection confirmed that these activities had improved community skills, expanded understanding of waste management, and opened opportunities for sustainable home-based enterprises. This study demonstrated that a participatory approach effectively addressed environmental issues and supported local economic empowerment.